Relationship between organizational innovativeness types and organizational effectiveness in private universities in Iran - Ashraf, Giti; Abd Kadir, Suhaida; Lope Pihie, Zaidatol Akmaliah; Mat Rashid, Abdullah (Macrothink Institute, Inc., 2014)
Empirical evidences indicate that if institutions of higher education are to survive and achieve long-run viability, they must be effective. Organizational innovativeness is viewed as an important factor for improving the organizational effectiveness in these organizations. The aim of this study was to examine the correlations between organizational innovativeness types and organizational effectiveness. The method used in the study was survey research. Based on cluster sampling method, 485 full time faculty members from Islamic Azad University, Iran, were selected as the respondents of the study. Two questionnaires were developed according to an extensive review of literature for measuring organizational innovativeness types and organizational effectiveness. The results indicated that both technical and administrative innovations positively and significantly predicted organizational effectiveness. Therefore, universities must implement administrative and technical innovations to improve organizational effectiveness. However, each type of innovativeness affects different aspects of organizational performance.